2008
DOI: 10.1074/jbc.m800649200
|View full text |Cite
|
Sign up to set email alerts
|

SDF1α/CXCR4 Signaling, via ERKs and the Transcription Factor Egr1, Induces Expression of a 67-kDa Form of Glutamic Acid Decarboxylase in Embryonic Hippocampal Neurons

Abstract: Stromal cell-derived factor ␣ (SDF1␣) and its cognate receptor CXCR4 play an important role in neuronal development in the hippocampus, but the genes directly regulated by SDF1␣/ CXCR4 signaling are unknown. To study the role of CXCR4 targeted genes in neuronal development, we used neuronal cultures established from embryonic day 18 rats. Hippocampal neurons express CXCR4 receptor proteins and are stimulated by SDF1␣ resulting in activation of extracellular signal-regulated kinase (ERK)1/2 and the transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 67 publications
(63 reference statements)
3
50
0
Order By: Relevance
“…The effect of 5-HT on GAD1 expression in hippocampal neuronal cultures was mimicked by NGFI-A overexpression. This finding is consistent with that of a report showing that SDF1␣-induced increases in GAD1 expression in cultured hippocampal neurons are mediated by an increased association of NGFI-A to the GAD1 promoter (Luo et al, 2008). These findings replicate previous results showing that maternally induced increases in NGFI-A expression are associated with an increase in NGFI-A association with NGFI-A-sensitive promoters, and stable epigenetic alterations (Weaver et al, 2004b(Weaver et al, , 2007.…”
Section: Discussionsupporting
confidence: 83%
“…The effect of 5-HT on GAD1 expression in hippocampal neuronal cultures was mimicked by NGFI-A overexpression. This finding is consistent with that of a report showing that SDF1␣-induced increases in GAD1 expression in cultured hippocampal neurons are mediated by an increased association of NGFI-A to the GAD1 promoter (Luo et al, 2008). These findings replicate previous results showing that maternally induced increases in NGFI-A expression are associated with an increase in NGFI-A association with NGFI-A-sensitive promoters, and stable epigenetic alterations (Weaver et al, 2004b(Weaver et al, , 2007.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have shown that the binding of CXCL12 to CXCR4 activates multiple intracellular signaling pathways, including the ERK pathway [32], so we assessed ERK activation in the spinal cord following SNI. The level of p-ERK increased on day 1, peaked on days 3 and 7, and lasted for 3 weeks after SNI (Fig.…”
Section: Cxcl12/cxcr4 Signaling-mediated Neuropathic Pain Depends On mentioning
confidence: 99%
“…In a primary astrocyte culture model, Han et al showed that CXCL12 stimulation triggers the activation of NF-jB and ERK, and that both of these contribute to the secretion of TNF-a [9]. In cultured hippocampal neurons, CXCL12-induced GAD67 (a key enzyme in GABA synthesis) expression is mediated by the G-protein-coupled CXCR4 and activation of the ERK pathway [32]. These results imply that ERK might be an important signal in CXCR4-mediated neuromodulation, and our present results provide evidence that spinal ERK activation contributes to CXCL12/CXCR4-mediated neuropathic pain.…”
Section: Intracellular Signaling Pathway Of Cxcl12-mediated Neuropathmentioning
confidence: 99%
“…This is an important distinction to make, as there are multiple signaling pathways that could potentially influence CXCR4-mediated chemotaxis. Cell migration due to CXCR4 activation is the result of activation of multiple signaling pathways [133][134][135], including the ERK1/2, JNK, MAPK, and GSK 3a/~ phosphorylation systems, [129] activation of phospholipase C to enhance calcium mobilization [130], activation of the phosphoinositide-3-kinase pathway to activate AKT [130], and activation of PKa or CREB [131,132]. Thus anti-chemotaxis activity of ECl VS 14…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the G~y subunit also results in signaling by the Phospholipase C pathway to enhance calcium mobilization as well as signaling by the Phosphoinositide-3-kinase pathway to activate AKT. CXCR4 binding of CXCL 12 also serves to augment intracellular cAMP levels [130] and activate cAMP-dependant signaling pathways, such as PKa or CREB [131,132]. The combined activation of these factors results in cell migration [133][134][135].…”
Section: Cxcr4/cxcl 12 Signaling Occurs By a Variety Of Pathwaysmentioning
confidence: 99%